PELATIHAN PENGOLAHAN LIMBAH KULIT PISANG MENJADI PUPUK DENGAN PENGEMASAN YANG ERGONOMIS HINGGA PADA PENCIPTAAN HILIRISASI PRODUK AGROINDUSTRI - Sukandar, Rani Septiani; Jumhana, Enjum; Salvano, Rudi Atoric (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Banana peel is a waste that is rarely used and thrown away. Therefore, it is necessary to find a treatment solution by utilizing banana peels into a product that is valuable and has selling value. Downstreaming has several benefits, namely to provide added value to products, create new jobs, and optimize the use of available natural resources. So it can minimize the waste produced. Thus, downstreaming can also provide environmental benefits and better sustainability of natural resources. The implementation of the dedication of lecturers and students through training in processing banana peel waste into fertilizer, was carried out in Pegandikan Village, Lebak Wangi District, Serang Regency. Participants in the training activity on processing banana peel waste into fertilizer were several residents of Pegandikan village who are members of the KUBE Berseri Waste Bank. This training activity is able to provide information and understanding that banana peel waste can still be utilized. One of them can be made into organic fertilizer. The success of the service team in raising the interest of Pegandikan villagers to start a new independent entrepreneur, namely the business of making pure banana peel fertilizer. The selection of ergonomic and simple packaging can be a solution in product packaging. With the label used, pay attention to honesty and be able to contain complete information. The packaging used is used bottles so as to reduce production costs. Sales, which are carried out through a point-of-sale system at various plant and fertilizer kiosks, are expected to be able to attract new partnerships for collaboration in the future. By offering attractive sales methods to consumers, namely by implementing a bundling system. A bundle package is made with other products such as pots, plants, or with other types of fertilizers. The KUBE Berseri Waste Bank members looked enthusiastic during the activity and looked happy when they succeeded in processing banana peel waste from start to finish. This can be seen from the creative ideas expressed by the participants regarding the development of homogeneous product compositions, which could one day be made heterogeneous. There are also several expressions related to product packaging innovation that are more interesting